HUBUNGAN UPAYA PREVENTIF DALAM SEKSUAL MENYIMPANG PADA REMAJA DENGAN RESIKO PEYIMPANGAN SEKSUAL DI SMA IMELDA MEDAN - Damanik, Hamonangan; Manurung, Sarida Surya; Sagala, Deddy Sepadha Putra; Ritonga, Edisyah Putra; Naibaho, Eka Nugraha V; Siburian, Christine H (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2023)
Sexual deviant behavior is also called abnormal or unnatural sexual behavior and has a tendency to lead to sexual crimes (Suherman, 2013). Deviant sexual behavior in question includes homosexuality (gays and lesbians), transexualism, sadism, masochism, sodomy, exhibitionism, voyeurism, bestialism, fetishism, incest, necrophilia, transvestism, sexualism, pedophilia, saliromania, frottage, mysophilia, and telephone scatologia. This study aims to analyze the relationship between preventive efforts (sex education) in sexual deviance in adolescents and the risk of sexual deviance at Imelda High School, Medan. The type of research used is descriptive correlation with a cross sectional study design. The research was conducted in July 2020. The population in this study was all students in class XI and XII of SMA Imelda Medan totaling 175 people. The sampling technique in this study was a proportional stratified random sampling technique, so the number of samples in this study was 30 people. The results of the research show that there is a relationship between preventive efforts for sexual deviance in adolescents and the risk of sexual deviance at Imelda High School, Medan. This is proven by the results of the chi square statistical test which obtained a significant number or probability value (0.031) which is lower than the significant standard of 0.05. It is hoped that teenagers understand the risks of sexual deviance and can control themselves with prevention efforts that have been provided through schools, families and communities in the form of sex education so that they do not easily fall into sexual deviant behavior that will harm themselves.